Isolation and Diagnosis of Multi Drug Resistance Pseudomonas Aeruginosa from Wound and Burnpatients in Baghdad City - Mustafa Riyadh Salman AL-Rubaye1 , Taghreed Khudhur Mohammed2 , Hanaa N. Abdullah3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Pseudomonas is a common bacteria found all over the world; in soil,water, and plants, and it is one of the most common pathogens in hospital-acquired infections. Aims: The aims of this study were isolation of P. aeruginosa bacteria from patients with inflammation of burns, Diagnosis and identification of P. aeruginosa using chemical tests and VITEK2 system and alsostudy of antibiotic resistance in P. aeruginosa using the VITEK2 system. Method: (206) swabs were collected from wounds and burns; (139) samples from burns and (67) samples from wounds; from different clinical cases for both sexes and ages (1-70) years, the patients coming and sleeping in Baghdad Teaching Hospital and Burns Hospital in the City of Medicine at Baghdad city; the duration from January to the end of March 2019. Samples were cultured on the variety of culture media (MacConkey agar, Blood agar and Cetrimide agar) in order to obtain the bacterial isolates of P. aeruginosa depending on their phenotypic characteristics.VITEK2 system were used for identification P. aeruginosaand to study their resistance to the antibiotics. Results: Out of the 206 samples, 50 Pseudomonas aeruginosa were isolated from swabs. 31(62%) isolates were isolated from burn and 19 (38%) from wound swabs. The isolates were subjected to a series of biochemical tests as diagnosed with Api 20E; and VITEK2 system to increase confirmation of isolation yield for P. aeruginosa bacteria. The results showed that the majority of isolates were (92%) resistant to Amoxicillin while the isolates differed between sensitive and moderate sensitivity and resistance to other types of antibiotics. Conclusion: The study showed that the percentage of isolation of Pseudomonas aeruginosa bacteria from wound infections is relatively higher than the rate of isolation from burn swabs. Most of Pseudomonas aeruginosa isolates showed high resistance to most types of antibiotics used in the present study, especially the antibiotic Amoxicillin where the resistance rate was 92%.